Strategi Guru Pembimbing Mengatasi Kenakalan Siswa Usia Puberttas di Sekolah Menengah Pertama (SMP) Negeri 10 Sijunjung - Zahara, Rita; Pasilaputra, Dodi (Al-DYAS, 2023)
Social relations between male students and female students exceed the limit, are often late, act indifferent and take it easy when scolded by picket teachers. The aim of the study was to find out the strategies used by supervising teachers in dealing with the delinquency of pubertal students at SMPN 10 Sijunjung. The research method is descriptive qualitative, the key informants in this study were the Coordinator of Guidance Teachers at SMPN 10 Sijunjung, supporting informants namely school principals, subject teachers, homeroom teachers and students. Based on the research conducted, it can be stated that the guidance counselor at SMPN 10 Sijunjung has carried out alleviation of student delinquency, which is carried out through the implementation of individual counseling services, through group guidance services and through mediation services. In general it can be said that these three services have been implemented well in overcoming student delinquency, and alleviation of student delinquency at SMPN 10 Sijunjung is also carried out by increasing collaboration with student parents. In this case the school invites parents to come to school once every quarter. In the meeting discussed jointly solutions that can be done in overcoming student delinquency. From the description above, it can be concluded that the counseling teacher has carried out various strategies in dealing with student delinquency at SMPN 10 Sijunjung.